Knowledge of environmental protection and discrimination in the Aymara communities of Ilave - Alanoca, Vicente (2018)
The environmental crisis is a problem that interests all the peoples of the planet. However, there are peoples and cultures that are facing this issue from their organizational forms. The objective of this research was to identify and describe the knowledge and practices of environmental protection in the Aymara communities of the district of Ilave, province of El Collao (Puno-Peru). The ethnographic and hermeneutic method has been used, resorting to the participant-observation technique, interviewing community leaders, elders and experts in the three zones of the district during the 2016-2017 period. Likewise, the historical process and the contextualisation of the habitual spaces of discrimination have been analyzed. The results of the study show the use of the different strategies of environmental protection still in force, in spite of the homogenization efforts of the cultural practices of environmental protection by the different development programs and the academy. This knowledge is weighted in the raising of the "mother earth", since the forms of Aymara experience are founded on it. This knowledge constitutes a strength and sustains the power of local organizations, they are activated when they are affected or attacked. These have become alternatives and hopes in the face of the social and environmental collapse that society suffers.